Iqbal’s Vision of Spiritual Selfhood and the Ethical Challenges of Transhumanist Education Futures - Fakhar-Ul-Zaman; Rabiya Javaid; Nazash Parvaiz (Journal of Religion and Society, 2025)
Education systems increasingly embrace transhumanist ideals such as artificial intelligence, cognitive enhancement, and genetic modification they risk sidelining the spiritual, ethical, and cultural aspects of human development. This is particularly critical in non-Western contexts like Pakistan, where education has traditionally been intertwined with religious, philosophical, and ethical foundations. This study addresses this tension by exploring how Allama Iqbal’s vision of spiritual selfhood can provide a counter-narrative to the ethical void and existential concerns found in transhumanist educational futures. The research aimed to: (1) explore Iqbal’s concept of Khudi (selfhood) and its philosophical roots, (2) critically analyze the ethical assumptions within transhumanist educational discourse, and (3) examine whether Iqbal’s thought challenges or complements these models. A qualitative interpretive design was used, grounded in philosophical inquiry and critical discourse analysis (CDA). Data were collected through secondary sources, including textual analysis of Iqbal’s works The Reconstruction of Religious Thought in Islam, Bang-e-Dra, Bal-e-Jibril, and Zarb-e-Kalim and content analysis of major transhumanist literature by thinkers like Bostrom, More, Vita-More, and Peters. Data were coded thematically into three categories: (1) philosophical themes in Iqbal’s selfhood, (2) ethical assumptions in transhumanist discourse, and (3) points of convergence and conflict between the two. A purposive sample of 20 key sources was selected. Findings reveal that Iqbal’s emphasis on spiritual agency, moral responsibility, and purposeful autonomy offers an ethical framework capable of grounding educational futures in values beyond technological progress. The study encourages integrating indigenous philosophical thought to balance innovation with ethical-spiritual growth Keywords: Iqbal’s Vision, Spiritual Selfhood, Ethical Challenges, Transhumanist Education Futures